In Solitary Rabbits, Does the Presence or Absence of a Mirror Affect Stress, Fear and Anxiety? - Schofield, Rebecca (Veterinary Evidence, 2019)
There is an erratum to this paper published in Veterinary Evidence Vol 4, Issue 2 (2018): http://dx.doi.org/10.18849/ve.v4i2.262 PICO question In solitary rabbits, does the presence or absence of a mirror affect stress, fear and anxiety? Clinical bottom line Four studies were reviewed in this knowledge summary. Despite the small number of papers available, the controlled trials and their methodologies provide strong evidence that the behavior of solitary laboratory rabbits is affected by the presence or absence of mirrors. This evidence also indicates an effect on their welfare. The studies suggest that the presence of mirrors provides environmental enrichment and have a positive effect on the subjects health and welfare. However, it is also suggested that mirrors may have some detrimental physical and psychological effects for some individuals. There are also many gaps in the available research and these need to be addressed to give better insight into the effect of mirrors on rabbits. Because of the current level of knowledge, clinical recommendations cannot be made at present on the use of mirrors in solitary rabbits to improve their veterinary care whilst hospitalised.